An Analysis of the Role of Highly Educated and Career Women in Household Welfare - Fadhilatus Sa'adah; Hudzaifah, Ayu; Maharani, Alda (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2025)
This study aims to analyze the role of educated and career-oriented women in maintaining household welfare. The main focus of this research is how women with a high level of education and a successful career can fulfill dual roles as homemakers and professionals without neglecting their family responsibilities. This study employs a qualitative approach using descriptive methods to systematically and factually describe the phenomenon. Data were collected from various sources, including academic journals, articles, and relevant books. The findings reveal that women with higher education and successful careers contribute significantly to household welfare, including economic support, children's education, and family relationships. From an Islamic perspective, women can work as long as they do not neglect their duties as wives and mothers. This dual role also supports the achievement of maqashid al-shari'ah, which includes preserving religion, life, intellect, lineage, and wealth. However, this study also highlights the challenges faced by women in performing dual roles, such as role conflicts, limited time for family, and social pressures. Therefore, support from partners and the social environment is essential to creating harmony between a woman's household life and career.